In silico design of refined ferritin-SARS-CoV-2 glyco-RBD nanoparticle vaccine - Masoomi Nomandan, Seyedeh Zeinab; Azimzadeh Irani, Maryam; Hosseini, Seyed Masoud (Frontiers in Molecular Biosciences, 2022)
With the onset of the Coronavirus disease 2019 (COVID-19) pandemic, all attention was drawn to finding solutions to cure the coronavirus disease. Among all vaccination strategies, the nanoparticle vaccine has been shown to stimulate the immune system and provide optimal immunity to the virus in a single dose. Ferritin is a reliable self-assembled nanoparticle platform for vaccine production that has already been used in experimental studies. Furthermore, glycosylation plays a crucial role in the design of antibodies and vaccines and is an essential element in developing effective subunit vaccines. In this computational study, ferritin nanoparticles and glycosylation, which are two unique facets of vaccine design, were used to model improved nanoparticle vaccines for the first time. In this regard, molecular modeling and molecular dynamics simulation were carried out to construct three atomistic models of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Receptor Binding Domain (RBD)-Ferritin nanoparticle vaccine, including unglycosylated, glycosylated, and modified with additional O-glycans at the Ferritin-RBD interface. It was shown that the Ferritin-RBD complex becomes more stable when glycans are added to the Ferritin-RBD interface and optimal performance of this nanoparticle can be achieved. If validated experimentally, these findings could improve the design of nanoparticles against all microbial infections.